The students' preferences on the use of writing strategies at universitas PGRI Wiranegara - Nurjanah, Nanda; Mabaroh, Barotun; Pusparini, Diah Anita (Mell Baou Publisher, 2025)
Writing is a crucial skill in English that significantly influences overall language proficiency. The effective use of writing strategies can greatly impact students' writing abilities. This study aimed to explore students' preferences for writing strategies to help lecturers better understand and align their teaching methods with the strategies students tend to use. The research was conducted at Universitas PGRI Wiranegara from June 4th to 24th, 2024, involving 69 English students. The study employed a descriptive quantitative approach, utilizing surveys to gather data on students' writing strategies. The results revealed that most students are familiar with and often apply various strategies during their writing activities. Out of the 35 strategies presented across three different theoretical frameworks, students reported using 33 of them, although not consistently in every writing task. The most commonly used strategy, according to the Likert scale, was